Spatially resolved acoustic spectroscopy for selective laser melting - Smith, Richard J.; Hirsch, Matthias; Patel, Rikesh; Li, Wenqi; Clare, Adam T.; Sharples, Steve D. (Elsevier, 2016)
Additive manufacturing (AM) is a manufacturing technique that typically builds parts layer by layer, for example, in the case of selective laser melted (SLM) material by fusing layers of metal powder. This allows the construction of complex geometry parts, which, in some cases cannot be made by traditional manufacturing routes. Complex parts can be difficult to inspect for material conformity and defects which are limiting widespread adoption especially in high performance arenas. Spatially resolved acoustic spectroscopy (SRAS) is a technique for material characterisation based on robustly measuring the surface acoustic wave velocity. Here the SRAS technique is applied to prepare additively manufactured material to measure the material properties and identify defects. Results are presented tracking the increase in the measured velocity with the build power of the selective laser melting machine. Surface and subsurface defect measurements (to a depth of ∼24 μm) are compared to electron microscopy and X-ray computed tomography. It has been found that pore size remains the same for 140 W to 190 W melting power (mean: 115–119 μm optical and 134–137 μm velocity) but the number of pores increase significantly (70–126 optical, 95–182 velocity) with lower melting power, reducing overall material density.